Development of locomotor movement learning media based on games in physical education learning at elementary schools - Gusnaweti Gusnaweti; Umar Umar; Anton Komaini; Aldo Naza Putra (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study addresses the low motivation of elementary students in Physical Education, Sports, and Health (PJOK) caused by conventional teaching methods. It aims to develop a game-based locomotor movement learning media for Public Elementary School 07 Tiumang, Dharmasraya Regency. A Research and Development (R&D) design was applied using the ADDIE model, with needs analysis, media design, expert validation, classroom implementation, and evaluation. Expert validation covered media, material, and language aspects, while student responses assessed practicality. Results showed high validity: media 96.25%, material 95.42%, and language 84.44%, and high practicality with 99% positive student responses, indicating the media is feasible and engaging. This game-based media supports student-centered learning, increases motivation and participation, and provides PJOK teachers with a practical tool to enhance learning quality in elementary school contexts.